FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TERJADINYA TANAH ABSENTEE DAN DAMPAKNYA BAGI MASYARAKAT DI KECAMATAN BINUANG KABUPATEN POLEWALI MANDAR - Syamsu Alam Hamid (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2014)
Relating absentee land ownership, the rule refers to the implementation of Law No. 5 of 1960 on the Basic Principles of Regulation Agraia (BAL) The government passed Law 56 Prp 1960 on Hold Size Determination Farms with implementation of PP No. 224 of 1961 on the Implementation of Land Distribution and Compensation Division, in article 3, paragraph (1) PP 224 of 1961 in conjunction with Article 1 PP 41 of 1964 stipulates the prohibition of land ownership In Absentee, which states that "ownership of agricultural land by people who live outside the districts where geography is prohibited, namely that farmers actively and effectively in work on his farm land so that productivity can be increased. This study used a sociological juridical approach through qualitative descriptive analysis is an approach that is conducted to analyze the extent to which a rule / law or the law being applied effectively. The results showed the ban on absentee land ownership in the District Binuang has yet to be implemented effectively.